Plant uses by the Topnaar of the Kuiseb Valley Namib Desert - Van Damme, Patrick; van Den Eynden, Veerle; Vernemmen, Patrick (Afrika Focus, 1992)
The Kuiseb Topnaar use some 50 different plants for food, woodfuel, cosmetics, as drugs, for construction, . . . . The different plants are presented here and their uses discussed and compared to uses in other settings.